Quantifying Complications: An Analysis of Operative Time and Intraoperative Factors in Microsurgical Breast Reconstruction - Egan, Katie G.; Elver, Ashlie A.; Godbe, Kerilyn N.; Nazir, Niaman; Holding, Julie; Butterworth, James; Lai, Eric (Journal of Reconstructive Microsurgery, 2022)
Background Analysis of operative flow has been shown to improve efficiency in breast microsurgery. Both complex decision-making skills and technical mastery are required to overcome intraoperative challenges encountered during microsurgical reconstruction. Effects of intraoperative complications on operative time have not yet been reported.Methods A retrospective chart review of microsurgical breast reconstructions by three surgeons between 2013–2020 analyzed operative variables and duration. Intraoperative complications were determined from the operative report. Correlations between continuous variables were determined using Spearman correlation coefficients. Nonparametric testing was used when comparing operative duration between groups.Results Operative duration was analyzed for 547 autologous breast reconstruction cases; 210 reconstructions were unilateral and 337 were bilateral. Average operative duration was 471.2 SD 132.2 minutes overall (360.1 SD 100.5 minutes for unilateral cases and 530.5 SD 110.5 minutes for bilateral cases). Operative duration decreased with surgeon experience (r = -0.17, p< .001).Regarding intraoperative complications, difficult donor dissection was correlated with an average operative duration increase of 91.7 minutes (n = 43, 7.9%, p< .001), pedicle injury with an additional 67.7 minutes (n = 19, 3.5%, p = .02) and difficult recipient vessel dissection with an increase of 63.0 minutes (n = 35, 6.4%, p = .003). Complications with anastomosis also showed a statistically significant increase in operative duration, with arterial complications resulting in an increase of 104.3 minutes (n = 41, 7.5%, p< .001) and venous complications resulting in an increase in 78.8 minutes (n = 32, 5.8%, p< .001). Intraoperative thrombus resulted in an increase of 125.5 minutes (n = 20, 3.7%, p< .001), and requiring alternative venous outflow added an average of 193.7 minutes (n = 8, 1.5%, p< .001).Conclusion Intraoperative complications in autologous breast reconstruction significantly increase operative time. The greatest increase in operative time is seen with intraoperative thrombosis or requiring alternative venous outflow. As these complications are rarely encountered in breast microsurgery, opportunities for simulation and case-based practice exist to improve efficiency.
Keywords: microsurgery complications; operative time analysis; intraoperative complications; autologous breast reconstruction; microsurgery efficiency